Experimental extraction of the quantum effective action for a non-equilibrium many-body system - Prüfer, Maximilian; Zache, Torsten Victor; Kunkel, Philipp; Lannig, Stefan; Bonnin, Alexis; Strobel, Helmut; Berges, Jürgen; Oberthaler, Markus K. (Nature physics, 2020)
On the fundamental level, quantum fluctuations or entanglement lead to complex dynamical behaviour in many-body systems for which a description as emergent phenomena can be found within the framework of quantum field theory. A central quantity in these efforts, containing all information about the measurable physical properties, is the quantum effective action. Though non-equilibrium quantum dynamics can be exactly formulated in terms of the quantum effective action, finding solutions is in general beyond the capabilities of classical computers. Here, we present a strategy to determine the non-equilibrium quantum effective action using analogue quantum simulators, and demonstrate our method experimentally with a quasi-one-dimensional spinor Bose gas out of equilibrium.
Das PDF enthält zusätzlich einen Anhang von 7 Seiten
Gesehen am 23.06.2020